Upaya Peningkatan Hasil Belajar pada Materi Cerita Pendek Melalui Pembelajaran Saintifik Siswa Kelas IX SMP Negeri 23 Pekanbaru - Maryani, Maryani; Hanum, Zuraida; Dayanti, Nina; Yunelda, Yunelda; Rahayu, Titin Sami (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
The aim of this research is to enhance learning outcomes in short story material through scientific learning for Class IX students at SMP Negeri 23 Pekanbaru. Action Research methodology is employed, comprising two cycles: Planning, Implementation, Observation, and Reflection. The findings suggest effective strategies to elevate learning outcomes in short story material through scientific learning for Class IX students at SMP Negeri 23 Pekanbaru. Recommendations include encouraging teachers facing similar challenges to adopt Scientific Learning methods for improved outcomes and enhancing engagement by diversifying scientific learning approaches. This research contributes to the discourse on innovative teaching methodologies and underscores the importance of dynamic pedagogical approaches in optimizing student learning experiences.